The Urban Legacy Impacts of Mega-Event Stadia: Selected Case Studies from South Africa - Hilary K. N. BAMA; Tembi M. TICHAAWA (Editura Universităţii din Oradea, 2021)
This study considered the urban infrastructure legacy impacts of mega-events in the Global South with a specific focus on South Africa's 2010 stadia. By way of multiple case studies, undertaken in 2010 FIFA World Cup stadia in host cities Cape Town, Durban and Port Elizabeth, and applying a mixed-method approach, n=1120 urban residents living within a 2-km radius were surveyed in addition to interviews with key resource persons. The empirical findings indicate the existence of significant statistical differences in the perceptions of the urban residents and other stakeholder groups regarding the sustainability precepts that accompany the construction of stadia associated with the long-term urban infrastructure legacy implications. While the urban residents and the key resource persons agreed that the stadia had the potential to attract positive urban infrastructure legacy outcomes to their communities, one of the critical observations noted was the agreement that the costs associated with the maintenance and operations of these stadia were currently enormous, posing significant sustainability challenges and contentions. The study provides fresh insights into long-term mega-event urban infrastructure legacy impact assessment from a developing country perspective with innovative planning and strategy implications.